The association between isokinetic strength and strength asymmetry and jump performance in female volleyball players - Atik, B.; Ayberk, B.; Özgül, B.; Polat, M. G. (Sport Sciences for Health, 2024)
Purpose Since the use of normalized isokinetic strength was recently proposed to analyze sportive performance, it was aimed to examine relative isokinetic muscle strength as well as absolute strength in jump performance. Secondly, the investigation of the relationship between extremity-based and inter-extremity strength asymmetry and selected jump tasks was aimed.